PRINCIPLES AND GUARANTEES FOR THE LAWFUL APPLICATION OF TRADE DEFENCE MEASURES (European Journal of Interdisciplinary Research and Development, 2026)
Trade defence measures occupy a special and sensitive position within the legal order of the World Trade Organization. Anti-dumping duties, countervailing measures and safeguards allow WTO Members to react to dumped imports, subsidised imports or sudden increases in imports causing injury to a domestic industry. At the same time, these instruments operate as exceptions to the general framework of trade liberalisation and therefore require strict legal control. This article analyses the main principles and guarantees that determine the lawful application of trade defence measures under WTO law. It argues that the legality of such measures depends not only on the existence of dumping, subsidisation or increased imports, but also on compliance with procedural and evidentiary standards, including due process, transparency, confidentiality safeguards, objective examination, causation, non-attribution, proportionality, temporariness and effective review. Particular attention is paid to WTO dispute settlement practice, where panels and the Appellate Body have developed the standards of “positive evidence”, “objective examination”, “reasoned and adequate explanation” and “genuine and substantial relationship of cause and effect”. The article concludes that trade defence measures remain legitimate only when they function as disciplined corrective mechanisms and not as disguised instruments of protectionism.